The Role of Communication Ethics in Addressing Social Differences and Relational Challenges in the Digital Era - Andiga Pratama; Kiki Rahmayani; Muhammad Abduh Isma; Fikri Ramadhan; Ahmad Habbib Raziq (Academic Solution Publisher, 2025)
This study explores how ethical principles—such as honesty, empathy, responsibility, and dialogic respect—can address the growing challenges of online polarization, interpersonal conflict, and cultural fragmentation. Employing a qualitative literature review approach, this paper synthesizes insights from interdisciplinary sources spanning communication studies, media ethics, sociology, and digital literacy. The findings reveal that ethical communication is not only a theoretical construct but a practical necessity in digital ecosystems marked by anonymity, algorithmic bias, and declining civility. In particular, ethical frameworks rooted in dialogic theory and communicative action offer valuable strategies for navigating social differences and mitigating hostility. While challenges such as reduced empathy, shallow engagement, and institutional gaps persist, emerging opportunities exist through ethical platform design, digital education, and professional ethical leadership. Communication ethics, when embedded into policy, pedagogy, and everyday discourse, can transform online interaction into a space for inclusion, recognition, and relational healing. This study concludes that fostering ethically literate digital citizens is fundamental to achieving democratic engagement and sustainable peace in a digitally connected world. Communication must move beyond information transmission to become a vehicle for dignity, coexistence, and shared responsibility.